2016
DOI: 10.1002/chin.201603212
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Cell‐Free Protein Synthesis: Pros and Cons of Prokaryotic and Eukaryotic Systems

Abstract: Review: 177 refs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 139 publications
(187 reference statements)
0
8
0
1
Order By: Relevance
“…Comparing costs between prokaryotic lysate-based and eukaryotic lysate-based CFPS systems, it is demonstrated that despite the fact that prokaryotic CFPS systems are deficient in performing posttranslational modifications, they have proved to have higher yields at lower costs of extract preparation (Jin & Hong, 2018;Zemella et al, 2015). CFPS first generations suffered low protein expression yields and prolonged processing times due to nutrients/ energy depletion and waste-product accumulation, all of which have been resolved since the advent of continuous-flow formats (Katzen et al, 2005).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Comparing costs between prokaryotic lysate-based and eukaryotic lysate-based CFPS systems, it is demonstrated that despite the fact that prokaryotic CFPS systems are deficient in performing posttranslational modifications, they have proved to have higher yields at lower costs of extract preparation (Jin & Hong, 2018;Zemella et al, 2015). CFPS first generations suffered low protein expression yields and prolonged processing times due to nutrients/ energy depletion and waste-product accumulation, all of which have been resolved since the advent of continuous-flow formats (Katzen et al, 2005).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Extracts from prokaryotes (e.g., E. coli) and eukaryotes (e.g., wheat germ), along with rabbit reticulocytes and mammalian cell extracts have been widely used for protein synthesis in vitro (Bernhard & Tozawa, 2013;Endo & Sawasaki, 2006;Zemella, Thoring, Hoffmeister, & Kubick, 2015).…”
Section: A R Ia N T S Of Th E C a N O Ni C A L Eg G E X T R A C Tmentioning
confidence: 99%
“…Cell-free protein synthesis (CFPS) has gained much attention as an emerging technology in synthetic biology with a number of recent accounts in the literature (Chen and Jewett, 2016;Kahlig, 2014;Smith et al, 2014;Zemella et al, 2015). Among the many attractive attributes of CFPS as an alternative to cell-based protein expression methods (Swartz, 2012), is its demonstrated potential in possibly addressing the current need for on-demand, point-of-care production of protein biologics (Mohr et al, 2016;Pardee et al, 2016;Sullivan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive review (Zemella et al, 2015) compares various CFPS systems, which includes a detailed discussion of the advantages of using mammalian-based Chinese Hamster Ovary (CHO) cell extracts for the production of protein biologics over other well-known systems. For complex therapeutic proteins requiring post-translational modifications, a CHO-based CFPS system is an ideal platform for efficient, high-throughput synthesis.…”
Section: Introductionmentioning
confidence: 99%